Determinants of Trade Flows between Colombia and South Korea - Ariza Marin, Sandra Daniela (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper identifies the determinants of trade flows between Colombia and South Korea. For this purpose, the economic and commercial profile for both countries, bilateral trade and the signed FTA were analyzed. Likewise, a gravity model for total and sectorial trade with panel data for the period of 1993-2013 is applied, finding consistencies with the theoretical postulates. Variables such as income of the importer and exporter countries determine positive and significant bilateral trade, while the distance and landlocked decrease the likelihood of trade. Furthermore, the results of the gravity model indicate that the free trade agreements have no significant impact on trade of South Korea; however, from the analysis of the agreement it is considered that Colombian agricultural and agro-industrial products have potential opportunities to compete in the Asian country.